2023
DOI: 10.1007/s10459-022-10196-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of patient skin colour on diagnostic ability and confidence of medical students

Abstract: Previous literature has explored unconscious racial biases in clinical education and medicine, finding that people with darker skin tones can be underrepresented in learning resources and managed differently in a clinical setting. This study aimed to examine whether patient skin colour can affect the diagnostic ability and confidence of medical students, and their cognitive reasoning processes. We presented students with 12 different clinical presentations on both white skin (WS) and non-white skin (NWS). A th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Additionally, darker skin tones are generally underrepresented in medical education and teaching, further limiting clinicians' ability to recognise disease on skin of colour (Ebede & Papier, 2006; Nolen, 2020). Specific to LD, one study reported that students were more likely to diagnose LD accurately and confidently on white skin compared with non‐white skin (Dodd et al., 2023). It is also possible that there is less physician awareness of LD occurring in darker‐skinned patients or, perhaps, differential reporting of LD for some populations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, darker skin tones are generally underrepresented in medical education and teaching, further limiting clinicians' ability to recognise disease on skin of colour (Ebede & Papier, 2006; Nolen, 2020). Specific to LD, one study reported that students were more likely to diagnose LD accurately and confidently on white skin compared with non‐white skin (Dodd et al., 2023). It is also possible that there is less physician awareness of LD occurring in darker‐skinned patients or, perhaps, differential reporting of LD for some populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent dermatological study concluded that the limited representation of skin tones within educational resources showing skin pathologies and clinical signs hindered medical students' diagnostic abilities and their confidence in diagnosing patients with darker skin. 11 In contrast, a similar study showed that exposure to dermatological pathology on darker skin increased physician's confidence in diagnosing rashes and had the potential to improve patient outcomes. 12 Given that gross anatomy is commonly delivered at the onset of medical school, and often represents students' first in-depth exposure to human bodies from a clinical perspective, [13][14][15] the discipline is in a unique position to mitigate biases and stigmas by developing a culture of diversity and inclusion through its educational resources, and by introducing targeted initiatives throughout its delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Limited exposure to diverse populations through interpersonal relationships and/or instructional materials may surface as learning deficiencies and, thus, curb one's abilities to deliver the highest quality care. For example, a recent dermatological study concluded that the limited representation of skin tones within educational resources showing skin pathologies and clinical signs hindered medical students' diagnostic abilities and their confidence in diagnosing patients with darker skin 11 . In contrast, a similar study showed that exposure to dermatological pathology on darker skin increased physician's confidence in diagnosing rashes and had the potential to improve patient outcomes 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Skin changes in hyperthyroidism vary from individual to individual [4]. In dark skinned Africans it may be challenging to detect these dermatoses and care for the patients with these dermatoses if they arise [5]. Making the actual cutaneous diagnosis in hyperthyroidism may be impaired by co-morbidities, drug-drug interactions, hypersensitive reactions, unusual presentation of common diseases, immunosuppression that may result to opportunistic infections and similar presentations of dermatoses.…”
Section: Introductionmentioning
confidence: 99%